The Effect of a Modified GH11 Xylanase on Live Performance, Gut Health, and Clostridium perfringens Excretion of Broilers Fed Corn-Soy Diets - Nusairat, Basheer; Wang, Jeng-Jie (Frontiers in Veterinary Science, 2021)
Xylanase enzymes and other feed additives are being used more commonly in poultry feed to reduce feed cost, improve performance and maintain gut health. Five corn-soy-based dietary treatments were designed to compare the effect of different inclusion levels of high-efficiency GH11 xylanase on live performance, gut lesions, and environmental Clostridium perfringens load of broiler chickens. Diets were: standard diet (Positive control; PC); reduced energy by 130 kcal/kg diet (Negative control; NC); NC with xylanase at 10 XU/g of feed (NC+10); NC with xylanase at 12.5 XU/g of feed (NC+12.5); xylanase at 15 XU/g of feed (NC+15). Data were analyzed as one-way ANOVA. At 42 d, birds fed NC+12.5 and NC+15 were heavier (P<0.05) than NC and comparable to birds fed PC. Significant Improvement in FCR (P=0.0001) was observed from 1-42 d for NC+12.5 and NC+15 compared to NC. Supplementation of xylanase reduced (P<0.005) 21 d intestinal lesion score with further improvement (P<0.0001) at 42 d. NC+15 reduced lesion scores by 24% compared to NC. Xylanase supplementations reduced litter C. perfringens cell count compared to NC with the highest reduction of NC+15 treatment by approximately 27%. In conclusion, xylanase can be included in reduced-energy diets up to 15 XU/g of feed to improve live performance, energy digestibility, and reduce intestinal lesion scores in broilers.